Analisis Perilaku Pedagang Pasca Relokasi Pasar Dinoyo ke Merjosari - Tia Candra Dewi; Mit Witjaksono; Yohanes Hadi Soesilo (Jurnal Ekonomi dan Studi Pembangunan, 2015)
Study abaout relocation has effect on all stakeholders (stakeholders), where the greatest feeling the effects of the relocation to the merchant. With the change to a market location Dinoyo Merjosari much effect on the economic performance of traders. This study aims to determine impact relocation of the market Dinoyo to Merjosari for behavior merchant expectly performance trade. The survey results revealed that the economic performance of traders indicated by five (5) indicators of operating hours, quality merchandise, merchandise quantity, position shanties, and the ease of reaching the location. From 5 indicators, there are only 4 indicators were changed due to market movement of the market Dinoyo Merjosari is operating hours, quantity, position place to sell in market and reaching the location. The amendment then became the main cause of deterioration due to the economic capacity of traders drive up the cost and decrease turnover.Keywords: Impact Movement Location, Merchant Behavior